2015
DOI: 10.1103/physreve.91.052201
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics for a model of a confined quasi-two-dimensional granular gas

Abstract: The hydrodynamic equations for a model of a confined quasi-two-dimensional gas of smooth inelastic hard spheres are derived from the Boltzmann equation for the model, using a generalization of the Chapman-Enskog method. The heat and momentum fluxes are calculated to Navier-Stokes order, and the associated transport coefficients are explicitly determined as functions of the coefficient of normal restitution and the velocity parameter involved in the definition of the model. Also an Euler transport term contribu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 41 publications
3
45
0
Order By: Relevance
“…For the studied values of the parameters, it is found that Eq. (47) has no solution for ∆Tz ∆T > 0 and has one solution for ∆Tz ∆T < 0. In any case, even if the curves cross each other, it can happen that the initially hotter system crosses the stationary value and reaches the stationary state less quickly.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…For the studied values of the parameters, it is found that Eq. (47) has no solution for ∆Tz ∆T > 0 and has one solution for ∆Tz ∆T < 0. In any case, even if the curves cross each other, it can happen that the initially hotter system crosses the stationary value and reaches the stationary state less quickly.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Recently, the interest in the slit geometry with two parallel, hard plates of a single component system of hard spheres, with a separation between the two plates smaller than two particle diameters, has largely increased, due to a series of experimental observations in systems of macroscopic particles [9][10][11][12]. Although it is quite sure that the inelasticity of collisions, inherent to the macroscopic character of the spheres, and the subsequently needed energy injection to reach and maintain a steady state, play a crucial role in many of the observed features [13][14][15], it is clear that before considering the consequences of these factors, the idealized system of elastic hard spheres must be addressed. The central issue is whether it is possible to formulate a macroscopic, hydrodynamic-like theory to describe the two-dimensional dynamics of the system when observed from above or from below and, if the answer is affirmative, which is the form of the equations and the expressions of the coefficients appearing in them.…”
mentioning
confidence: 99%
“…The ideas of the method are the same as for ordinary granular gases [18]. The obtained hydrodynamic equations for the number density n(r, t), velocity flow u(r, t), and granular temperature T(r, t) read [19] …”
Section: Hydrodynamic Equationsmentioning
confidence: 99%
“…All these coefficients depend on the temperature, and also on the coefficient of normal restitution α and the characteristic speed ∆. Their expressions can be found in [19], and in a more concise way in the Appendix of [16]. They are given by the normal solutions-in the kinetic theory sense-of first-order partial differential equations.…”
Section: Hydrodynamic Equationsmentioning
confidence: 99%